Predicting peer acceptance among students with and without special educational needs in secondary educational settings - Douma, Ivonne; Warrens, Matthijs; de Boer, Anke; Minnaert, Alexander (Frontiers in Developmental Psychology, 2025)
IntroductionPeer acceptance is an important positive educational and social outcome for all students in inclusive secondary education, whether students have a disability or not. Peer acceptance is influenced by the educational setting and the peers educated in this setting. However, not much is known about the predictors of peer acceptance among students in secondary educational settings. The aim of this study was to examine predictors for peer acceptance on two levels, predictors on the individual level (i.e., behavioural problems and social skills reported by teachers) and the peer level (i.e., prosocial and aggressive behaviour, popularity and academic achievement reported by peers).MethodsFour groups of students (N = 344) educated in different secondary schools were included in the study. Two groups of typically developing students in secondary education (n = 248) and two groups of students in special secondary education with either an intellectual disability (n = 68) or students with social, emotional and behavioural difficulties (n = 28).ResultsUsing peer nominations in the data collection and multilevel analyses, the results showed no evidence for individual level predictors for peer acceptance for all four groups of students. On the peer level, popularity and aggression were found to predict peer acceptance among students in secondary education.DiscussionThe results of this study emphasise the essential role of peer perceptions in acquiring peer acceptance and the importance of fostering prosocial behaviour to promote peer acceptance in educational practices.